Are we Ready for Smart Cities? - Kornélia Lazányi (Interdisciplinary Description of Complex Systems, 2023)
Smart cities are an emerging phenomenon, which is not only called for by their inhabitant's needs, but also by the more and more pressuring external factors, such as global economic slowdown, the increasing scarcity of resources and climate change. While smart cities are to increase the quality of life of the people, often the people themselves are not ready, not smart enough for them. Technology readiness is an important factor of technology adaptation; hence it is the basis of whether people are looking forward to smart cities or are rather afraid of them. In the current article, the readiness of people in an international sample is assessed with the help of a questionnaire, but the understanding of their choices is enriched by cultural and economic background data stemming from two representative international surveys, namely the Cultural Dimensions research of Geert Hofstede and the Global Entrepreneurship Monitor data. The results presented in the article are in line with the international literature but are enriching the existing body by combining the socioeconomic and cultural aspects in the interpretation of individual choices.